2007
DOI: 10.4148/2378-5977.1532
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of human chorionic gonadotropin as a replacement for GnRH in an ovulation synchronization protocol before fixed-time insemination (2007)

Abstract: Two experiments were conducted to evaluate the difference between gonadotropinreleasing hormone (GnRH) and human chorionic gonadotropin (hCG) given at the beginning of a timed AI protocol and their effects on fertility. In Experiment 1, beef cows (n = 672) at six different locations were assigned randomly to treatments based on age, body condition, and days postpartum. On day −10, cattle were treated with GnRH or hCG and a progesterone-releasing controlled internal drug release (CIDR) insert was placed in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Similarly, when 1,000 IU of hCG replaced the first injection of GnRH of a CO-Synch + CIDR protocol, overall pregnancy rates were decreased (39 vs. 53%) in beef cows receiving hCG compared with those receiving GnRH (Burns et al, 2008). Differences in pregnancy rates were only observed in cows that were cyclic at the initiation of the estrus synchronization protocol (35 vs. 55% for hCG and GnRH, respectively) compared with those that were not cyclic at the initiation of the protocol (48 vs. 49% for hCG and GnRH, respectively; Burns et al, 2008). In our study, however, no treatment x cyclic status interaction was observed and heifers that were cyclic at the initiation of treatments had pregnancy rates similar to those of noncyclic heifers.…”
Section: Discussionmentioning
confidence: 86%
“…Similarly, when 1,000 IU of hCG replaced the first injection of GnRH of a CO-Synch + CIDR protocol, overall pregnancy rates were decreased (39 vs. 53%) in beef cows receiving hCG compared with those receiving GnRH (Burns et al, 2008). Differences in pregnancy rates were only observed in cows that were cyclic at the initiation of the estrus synchronization protocol (35 vs. 55% for hCG and GnRH, respectively) compared with those that were not cyclic at the initiation of the protocol (48 vs. 49% for hCG and GnRH, respectively; Burns et al, 2008). In our study, however, no treatment x cyclic status interaction was observed and heifers that were cyclic at the initiation of treatments had pregnancy rates similar to those of noncyclic heifers.…”
Section: Discussionmentioning
confidence: 86%